Lithography-free reconfigurable photonic processor - Ovvyan, Anna; Pernice, Wolfram (Nature photonics, 2023)
A lithography-free photonic processor through dynamic control of optical gain distributions is demonstrated, allowing reconfigurable photonic neural networks and more efficient signal processing, and showing great promise in easing data traffic as well as accelerating information processing speeds.